Expansion of the 'Antibiotic Guardian' one health behavioural campaign across Europe to tackle antibiotic resistance: pilot phase and analysis of AMR knowledge - Newitt, Sophie; Anthierens, Sibyl; Coenen, Samuel; Lo Fo Wong, Danilo; Salvi, Cristiana; Puleston, Richard; Ashiru-Oredope, Diane (Oxford University Press, 2018)
Antimicrobial resistance (AMR) is a major public health threat. The UK Antibiotic Guardian (AG) behavioural change campaign developed to tackle AMR was expanded across Europe through translation into Russian, Dutch and French. Demographics and knowledge of AGs were analyzed between 01 November 2016 and 31 December 2016. A total of 367 pledges were received with the majority from the public and health care professionals. The pilot has significantly increased the proportion of pledges from Europe (excluding UK) (chi2 = 108.7, P < 0.001). AMR knowledge was greater in AGs (including the public) compared to the EU Eurobarometer survey. Further promotion across Europe is required to measure an impact on tackling AMR.